Late payments in accession countries: Causes and international comparison - Janez Praésnikar; Marko Pahor; Andreja Cirman (The Journal of Entrepreneurial Finance and Business Ventures, 2004)
In developed countries in everyday business, payment delays often present a problem. Payment delays have already been a matter of discussion in Slovenia for several years. Irrespective of some positive movements in the past years, the state of payment discipline in Slovenia is not at a satisfactory level. In this area, Slovenia could be classified among the less successful countries when compared to other countries in Europe. Our paper determines factors behind this fact. The findings are important not only for Slovenia, but also for other EU candidate countries faced with similar problems of transition. The paper has led to the following conclusions. Firstly, the more indebted companies have longer payment delays. Secondly, the longer the contractual payment period, the shorter the payment delay. Longer payment periods are mostly received by larger companies. And thirdly, the longer the payment delays on the side of companies. buyers, the higher the incidence of late payments by the company. We can therefore conclude, based on our research, that payment delays in Slovenia depend mostly on risks involved with doing business with firms in financial distress, in particular with small businesses.
Keywords: 650